Developing Interventions for Frailty. (3rd February 2015) - Cameron, Ian D.; Fairhall, Nicola; Gill, Liz; Lockwood, Keri; Langron, Colleen; Aggar, Christina; Monaghan, Noeline; Kurrle, Susan
Abstract : Frailty is a well-recognised, complex syndrome, predominantly affecting older people. Currently, there are two main conceptualizations of frailty: the phenotypic and the accumulated deficit models, with the phenotypic model being more widely applied in clinical research. Based on these models, we contend that a number of the phenotypic frailty components (weakness, slowness, and low energy expenditure) are potentially reversible. This paper outlines the results of a frailty research program. It summarizes the initial frailty treatment model and reports its effectiveness. Briefly, the effect of a twelve-month individually tailored multifactorial, interdisciplinary intervention targeting frailty was compared with usual care. The intervention reduced phenotypically defined frailty and improved mobility. Further, it is contended that there is evidence of substantial unmet need due to treatment fragmentation and the absence of a comprehensive approach for this population. Our paper then outlines the current stage of our research in which the model is now being extended to prefrailty. Interventions aimed at reversing the frailty syndrome or its consequences are only in their early stages. There is significant scope for future research to identify optimal management programs for frail older people.